The Influence of Smart Visual Education Based on Dorothea Orem's Self-Care Theory on Anxiety Levels - Ismail, Nur; Haryanto, Joni; Veterini, Anna Surgean (Indonesian Journal of Global Health Research, 2024)
Anxiety is a feeling of discomfort, worry, fear, and tension. This response is a physiological response to external or internal stimuli that can cause behavioral, emotional, cognitive, and physical symptoms. Anxiety in patients starts from the moment the patient receives a surgery schedule. If the patient continues to feel anxious while the operation is in progress, this can disrupt the operation process because a tense patient can increase the heart rate which can affect the patient's blood pressure and breathing. This study aims to determine the effect of educational videos on anxiety in surgical patients. The research uses a quantitative research design with a quasi-experimental research design (pretest-posttest with control group design). There were 66 street children as respondents consisting of 33 control group respondents and 33 treatment group respondents. Respondents were determined using affordable population techniques. The independent variable is smart visual education based on Dorothea Orem's self-care theory and the dependent variable is anxiety level. Data was collected using a questionnaire and analyzed using the independent t-test with a significance level of p<0.05. The instrument used was the Amsterdam Preoperative Anxiety and Information Scale (APAIS) Questionnaire. There is a significant relationship between respondents' anxiety levels in the pretest and posttest results (p=0.000) in both the control group and the treatment group. However, there was no significant difference in the delta of respondents' anxiety levels in both the control and treatment groups. Smart visual education based on Dorothea Orem's self-care theory influences reducing the anxiety level of patients who will undergo surgery with SAB regional anesthesia.